Pengaruh tax avoidance, leverage, dan ukuran perusahaan terhadap kinerja perusahaan - Margareta Fitriani; Pujo Gunarso; Any Rustia Dewi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
Company performance is an achievement attained by the company during a specific time period that reflects the company's level of soundness. Company performance can be used as a measuring tool in assessing business success, as well as a factor in future decision making and planning. The study's goal is to examine the impact of tax avoidance, leverage, and company size on company performance. Purposive sampling was used in this study, which was conducted at a food and beverage company. According to the findings of this study, tax evasion has a negative impact on company performance. Leverage has a positive impact on business performance. The size of a company has a negative impact on its performance